ECONOMIC GROWTH AND REFORMS IN UZBEKISTAN: PATHS TO SUSTAINABLE DEVELOPMENT AND PROSPERITY - Khodjalepesov Polat Zinatdinovich; Muratbeva Sabira Bekmurzaevna; Mambetsharipova Gulzada Polatbaevna; Mirzabaeva Ulzada Quwanishbaevna (American Journals Publishing, 2025)
This article explores the main directions of economic growth and reforms in Uzbekistan aimed at improving the welfare of the people and optimizing government expenditures.
Keywords: Uzbekistan, economic growth, reforms, investment, macroeconomic indicators, international partnerships, tax administration, state budget, welfare state, education, healthcare.